Does Delayed Reexcision Affect Outcome After Unplanned Excision for Soft Tissue Sarcoma? - Han, Ilkyu (Springer-Verlag, 2010)
BACKGROUND: Unplanned excision of a soft tissue sarcoma generally requires reexcision to achieve an adequate surgical margin. Many surgeons assume delay of definitive surgery adversely affects patient survival and local recurrence. However, no clear evidence of this assumption can be found in the literature. QUESTIONS/PURPOSES: We asked whether delay in reexcision affects patient survival and local recurrence in reexcision after unplanned excision for soft tissue sarcoma. PATIENTS AND METHODS: We retrospectively reviewed 104 patients who underwent definitive surgery after unplanned excision of a localized soft tissue sarcoma. The average age of the patients was 44 years (range, 5–81 years). The most common diagnoses were malignant fibrous histiocytoma (36) and synovial sarcoma (22). Locations of the tumors were the lower extremity (62), upper extremity (32), and trunk (10). The median interval to definitive surgery was 32 days (interquartile range, 22–50 days). The minimum followup was 0.2 years (median, 4.7 years; range, 0.2–16.7 years). RESULTS: The 5-year disease-specific survival was 88% and 5-year local control rate was 74%. We found no difference in disease-specific survival or local recurrence according to the time until definitive surgery. Higher histologic grade and larger tumor size independently predicted disease-specific survival whereas a positive margin at reexcision and larger tumor size independently predicted local control. CONCLUSIONS: The data suggest any influence of delayed definitive surgery is likely to be of minor clinical importance. LEVEL OF EVIDENCE: Level III, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.